Reduced order multiscale modeling of fiber reinforced polymer composites including plasticity and damage. (August 2017) - Singh, Harpreet; Gupta, Mohit; Mahajan, Puneet
Highlights: A multiscale approach for fiber reinforced polymer composites is proposed which considers the plasticity and damage. The work includes the characterization of epoxy resins which show nonlinear stress-strain response due to damage and plasticity. Experiments were performed to demonstrate the damage and plasticity dependent behavior of matrix material as well as to validate the plasticity model. The proposed formulation is applied to study low velocity impact of E-glass/epoxy composite. The simulation results are validated with the experiments. Abstract: A multiscale procedure based on asymptotic expansion homogenization (AEH) technique is formulated to study the inelastic deformations and damage of fiber reinforced polymer composite materials (FRP). FRPs show significant inelastic deformation and local phase damage before the ultimate failure point and capturing these accurately using AEH is an active research area. The complex implementation and high computational cost of AEH when used in multiscaling can be alleviated by the reduced order techniques proposed by Oskay and Fish (2007). In the present work, the reduced order AEH formulation is extended to capture the plasticity and damage in the matrix. The initial studies are performed for representative volume element (RVE) which show the behavior as expected. This new formulation is applied to study the low velocity impact of composites. The results (force-time curves and extent of damage) are validated with experiments. The model is successfully able to capture the deflection at various points on the laminate plate and permanent indentation on the surface.